Injecting-related trust, cooperation, intimacy, and power as key factors influencing risk perception among drug injecting partnerships. - Meghan D Morris; Erin Andrew; Judy Y Tan; Lisa Maher; Colleen Hoff; Lynae Darbes; Kimberly Page (PLoS ONE, 2019)
Sharing of injection drug use paraphernalia is a dyadic process linked to the transmission of HIV and hepatitis C virus (HCV). Despite this, limited research exists identifying specific dyadic interpersonal factors driving injecting partners' engagement in needle/syringe and ancillary injecting equipment sharing among young adults. Using semi-structured in-depth interview data collected between 2014 and 2015 from twenty-seven people who inject drugs (PWID), we applied an inductive approach to identify key injection drug-related interpersonal factors and developed a conceptual model integrating the findings based on interdependence theory. Interactions between injecting partners resulted in varying levels of injecting-related trust, cooperation, intimacy, and power. These factors interacted to collectively influence the type and level of risk perceived and enacted by injecting partners. The relationship between these injecting-related interpersonal factors, on the one hand, and risk perception on the other was dynamic and fluctuated between actions that protect the self (person-centered) and those that protect the partnership (partnership-centered). These findings indicate that the interpersonal context exerts substantial influence that shapes risk perception in all types of injecting partnerships. Partnership-focused prevention strategies should consider the dynamics of trust, cooperation, intimacy, and power, in characterizing dyadic risk perceptions and in understanding risky injecting practices among PWID.